Do Developmental and Life-Course Theory Risk Factors Equally Predict Age of Onset Among Juvenile Sexual and Nonsexual Offenders?. (February 2020) - Rosa, Melanie; Fox, Bryanna; Jennings, Wesley G.
Previous empirical inquiries into the etiology of juvenile sex offending have been largely atheoretical. Consequently, a call for studies conducted utilizing developmental and life-course (DLC) criminological theory has been made to better understand the onset, development, risk, and protective factors of juvenile sex offending. Therefore, this study contributes to the discussion by testing key predictions proposed by the DLC framework regarding the theoretical correlates of early onset offending, as applied to juvenile sex offenders (JSOs) and juvenile nonsex offenders (JNSOs). Drawing on a data set of more than 64, 000 youth referred to the Florida Department of Juvenile Justice, results indicate that although the number and severity of risk factors for early age of onset differ between the JSOs and JNSOs, the specific type of risk factors that emerged align with DLC theory predictions. The implications of these findings and contributions for DLC theory are also discussed.